A comparative study on different surface balance training on dyanamic postural control in collegiate female athletes - J Kaur; Singh A; Grewal S (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2020)
Purpose: The study aims to evaluate the effectiveness of different surface balance training on dynamic posture control in collegiate female athletes. Methods: The research was experimental in nature. The subjects were selected through purposive sampling. 40 female collegiate students were selected and divided into 2 groups. Group A was given star excursion balance training on stable surface and Group B was given Star Excursion Balance Training on unstable surface. Pre and post protocol assessment was done with the help of YBT on day 1st and end of the 4th week. Results: Paired and Unpaired 't' test was applied for Mean and Standard Deviation (SD) comparison within and between the Group A and Group B for variable Y Balance Test (YBT). The mean±SD values of YBT within the groups were significant and between the Groups, Group B was statistically significant and Group A was statistically non significant. The results suggest that balance training on unstable surface is more effective in improving dynamic posture control among collegiate female athletes. Conclusion: The present study determined that unstable surface elicited the greater dynamic balance improvement compared to the stable surface. No such improvement was elicited in the stable surface which concluded that Star Excursion Balance Training will be effective as a dynamic balance improvement when it is performed on an unstable surface.